A cross-sectional study of antibiotic misuse among Chinese children in developed and less developed provinces - Yannan Xu; Jingjing Lu; Chenhui Sun; Xiaomin Wang; Yanhong Jessika Hu; Xudong Zhou (Journal of Infection in Developing Countries)
Introduction: Antimicrobial resistance is a global health crisis and primarily caused by antibiotic misuse. Antibiotic misuse among children is particularly concerning, and its prevalence may vary from region to region in China with different development levels.